NATURAL CORAL COLONIZATION OF A MARINA SEAWALL IN SINGAPORE - Chou Loke Ming; NG Chin Soon Lionel; Chan Sek Meng Jeremy; Seow Liyun Angie (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Marinas require extensive modification of a natural coast. The resulting modified habitat is known to supportchanged biological communities but the ability of tropical marinas to function as a surrogate habitat forscleractinian corals has not been well investigated. An assessment of scleractinian corals naturallycolonising a nine-year-old marina seawall in Singapore indicated 26 genera from 13 families, of whichPectinia and Turbinaria were the most dominant. Most colonies measured 10 – 25 cm in diameter. Reefs ofadjacent islands provided the larval source while the marina’s environmental conditions favored larvalrecruitment and growth. Specific larval settlement preferences as well as sediment rejection capabilities ofthe two most common genera could have contributed to their dominance. The study showed that the seawallof a marina can support scleractinian coral communities and with relevant management, can significantlyenhance marine biodiversity.